2022
DOI: 10.1016/j.matlet.2021.130908
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of diboride coatings by electrophoretic deposition in nanoparticle-containing molten inorganic salts

Abstract: Molten inorganic salts containing solid nanoparticles with a stable and uniform dispersion have attracted great attention as efficient heat transfer and storage materials 1,2 and for catalysis for chemical reactions [3][4][5] . Electrophoretic deposition in molten inorganic salts containing nanoparticles, have not been reported in the literature, compared with the related wide investigations in aqueous and organic suspensions 6,7 . Here we report the possibility of electrophoretic deposition of nanoparticles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…With higher magnification (Figure 2D), it seems that these micron-sized particles consist of a large number of nano-sized particles, which is similar to the results reported for EPD of ZrB 2 nanoparticles in NaCl-KCl-AlCl 3 melt. 12 Therefore, it can be concluded that in NaCl-KCl-AlCl 3 molten salts the EPD of TiB 2 nanoparticles could be achieved successfully, resulting in fabricating a dense and adhesive TiB 2 coating.…”
Section: Epd Of Tib 2 Coating In Nacl-kcl-alcl 3 Meltmentioning
confidence: 94%
See 4 more Smart Citations
“…With higher magnification (Figure 2D), it seems that these micron-sized particles consist of a large number of nano-sized particles, which is similar to the results reported for EPD of ZrB 2 nanoparticles in NaCl-KCl-AlCl 3 melt. 12 Therefore, it can be concluded that in NaCl-KCl-AlCl 3 molten salts the EPD of TiB 2 nanoparticles could be achieved successfully, resulting in fabricating a dense and adhesive TiB 2 coating.…”
Section: Epd Of Tib 2 Coating In Nacl-kcl-alcl 3 Meltmentioning
confidence: 94%
“…To avoid the decomposition of components of the electrolyte, we employed cell voltages below this value. So the applied cell voltage is selected in the range of 1.2–1.5 V. The detailed procedures could be referred to our previous studies 12 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations